Genesis of the Bairendaba Ag-Zn-Pb Deposit, Southern Great Xing’an Range, NE China: A Fluid Inclusion and Stable Isotope Study - Shunda Li; Keyong Wang; Yicun Wang; Xuebing Zhang; Hongyan Quan (Geofluids)
The Bairendaba deposit is the largest Ag-Zn-Pb deposit in Inner Mongolia. Vein and disseminated ores occur in biotite-plagioclase gneiss and quartz diorite along regional EW trending faults. Microthermometric data for H2O-NaCl ± CH4  ± CO2 fluid inclusions record a decrease in homogenization temperature and salinity of ore-forming fluids with time. Early and main-stage mineralization have homogenization temperatures of 242°–395°C and 173°–334°C, respectively, compared with 138°–213°C for late-stage mineralization. Fluid salinities for early mineralization have a bimodal distribution, dominantly 4.2–11.8 wt.% NaCl equivalent, with 35.2–37.8 wt.% NaCl equivalent for a small population of halite-bearing inclusions. Main- and late-stage fluids have salinities of 2.1–10.2 wt.% NaCl equivalent and 0.7–8.4 wt.% NaCl equivalent, respectively. Oxygen and hydrogen isotope data indicate the interaction of a magmatic fluid with wall rocks in early mineralization, followed by the introduction of meteoric water during late-stage mineralization. Values of –15.9‰ to –12‰ (δ13CPDB) for hydrothermal quartz indicate that organic-rich strata were the source of carbon. Sulfur had a magmatic source, based on values of –0.1‰ to 1.5‰ (δ34SV-CDT) for sulfide minerals. The Bairendaba deposit is a typical mesothermal system with mineralization controlled by structure.